Sistem Pembiayaan untuk Aplikasi teknologi pada Manajemen Rantai Pasok Hortikultura Bernilai Tinggi : Studi Kasus Pada Sistem Pembiayaan Greenhouse Paprika di Kabupaten Bandung Barat, Jawa Barat - Kusnandar Kusnandar; Tomy Perdana (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2014)
Until now, financing is still a problem for most farmers in developing country including Indonesia, especially for high value commodity such as pepper. Pepper cultivation requires high investment cost due to the necessity of pepper to grow in a greenhouse equipped with drip irrigation installation. Most farmers today utilizes greenhouses with appropriate technology. Even though favourable, the crop cannot reach optimal productivity. Meanwhile, Indonesian Vegetable Research Institute (Balitsa), cooperating with Wageningen University, has conducted a research to study a greenhouse design, optimal for Indonesian climate. However, the resulted greenhouse requires so high investment cost that most farmers cannot afford. Direct loan from banks is difficult to get because it requires guarantee and financing system, inappropriate with characteristics of farming. Due to that reason, it is necessary to have financing system that can help but does not burden farmers in its payment mechanism. This paper aims to analyze the financing system in supply chain management, capable to solve problems about financing access for small-scale business actor in order to apply a technology capable to increase productivity. This paper is written from the result of action research in Pasirlangu Village, Cisarua Subdistrict, West Bandung Regency. The result shows that the availability of partnerships between farmer groups/cooperation and exporters opens an opportunity for farmers to get loan from bank through guarantee from the exporters, with financing system regulated by exporters to fit the characteristic of pepper farming. The system also involves university as the facilitator.